In vitro growth of Dendrobium orchid on different concentrations of sucrose and myo-inositol - Rohman, Hanif Fatur; Rohman, Fadil; Firgiyanto, Refa; Ningsih, Riani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: The limitation of endosperm in seeds requires the propagation of Dendrobium orchid plants to be carried out using in vitro culture techniques. The composition of in vitro culture media needs to be considered because it greatly determines the success of plant propagation. The addition of sucrose and myo-inositol to the growth media can support the growth of explants planted in vitro. This study aimed to determine the best concentration of myo-inositol and sucrose added to the multiplication medium to increase the growth of Dendrobium orchid explants. Methods: This study used a Completely Randomized Design. The experimental treatments were the concentration of myo-inositol and sucrose added to the VW media consisting of four levels, namely myo-inositol 50 mg/l + sucrose 20 mg/l, myo-inositol 50 mg/l + sucrose 40 mg/l, myo-inositol 100 mg/l + sucrose 20 mg/l and myo-inositol 100 mg/l + sucrose 40 mg/l. Observation variables include plant height, shoot emergence time, number of shoots and shoot growth rate. Data were analyzed using analysis of variance (ANOVA) at 5% α level and Duncan's Multiple Range Test (DMRT) at 5% level. Results: The addition of 40 g/l sucrose + 50 mg/l myo-inositol to the in vitro culture medium was the best treatment in producing optimal explant growth. Conclusion: The addition of 40 g/l sucrose can reduce the addition of myo-inositol to VW media by up to 50% to propagate Dendrobium orchids in vitro.